Análisis, diseño e implementación de hardware lúdico interactivo en el desarrollo cognitivo de la estimulación temprana, control biométrico y aplicación web en el CIBV del MIES Fernando Ugarte de la ciudad de Machala. - Briones Nuñez, Felipe Ignacio (2014)
The Ministry of Economic and Social (MIES) Education to help in child development in the city of Machala is in charge of the Children's Center of Good Living (CIBV) "Fernando Ugarte," where there are early learning programs for children from 0 to 3 years, but the monitoring and control of the development had been doing manually; causing overwork for the educator and feedback to parents were not given in adequate time.